Islamic Family System: A Message of Love, Cooperation, and Justice: اسلامی خاندانی نظام: محبت، تعاون اور عدل کا پیغام - Islam, Muhammad Umar; Nazir, Dr. Ruqayya (Al Khadim Research Journal of Islamic Culture and Civilization, 2025)
The Islamic family system is a comprehensive system based on love, cooperation, and justice. The Quran and Sunnah teach us to create a family in which each individual is given their due and all are bound together by mutual respect, love, and compassion. Islam has considered the relationship between husband and wife to be not just a physical or social contract but a sacred covenant. Love (mawada), mercy (rahmatullahi alaihi wa sallam) and tranquility (sakina) are the basic elements of this relationship. The Quran states: “And He created for you mates from among yourselves that you may find tranquility in them, and He has put between you love and mercy." (Surah Ar-Rum: 21) In the Islamic family system, rights and duties have been determined between parents, children, wife, husband and other relatives so that no one is subjected to injustice. The husband is presented as the Qawam (caretaker) and the woman as the caretaker of the house, but the relationship between the two is based on mutual advice, respect and justice. Elements such as the upbringing of children, respect for elders, kindness to relatives, and the rights of neighbors shape this system into a coherent and balanced social structure. The Islamic family system is not only a means of spiritual and social development of the individual but also a means of establishing peace, tranquility, and justice in the entire society.